Manganese peroxidase and biomimetic systems applied to in vitro lignin degradation in Eucalyptus grandis milled wood and kraft pulps - Masarin, Fernando [UNESP]; Norambuena, Marcela; Ramires, Heloisa O. R.; Demuner, Braz J.; Pavan, Paulo C.; Ferraz, Andre (Wiley-Blackwell, 2016)
BACKGROUNDOrganoperoxyl radicals generated from unsaturated fatty acids can initiate lignin degradation reactions. RESULTSManganese peroxidase (MnP, EC 1.11.1.13) produced by the basidiomycete Ceriporiopsis subvermispora and biomimetic systems were explored to produce organoperoxyl radicals for lignin degradation of eucalypt wood and unbleached kraft pulps. Treatment of milled-wood with MnP-, Mn3+- or Fe2+-linoleic acid systems transformed the lignin structure and released water-soluble low molar mass aromatic fragments. Lignin transformations initiated by MnP were the most intense. Residual lignins from MnP- or Mn3+-treated wood exhibited diminished yields for thioacidolysis monomers and increased carboxyl content, suggesting -O-4 and C-C cleavage followed by side chain oxidation. MnP-based biobleaching of eucalypt kraft pulp corresponded to savings of 3.7 kg ClO2 ton(-1) pulp during elemental chlorine free (ECF) bleaching to 88-90% brightness. Another interesting characteristic of the MnP-treated pulp was a slightly higher drainage before refining, suggesting that this pulp would require less energy during drying in industrial processes. CONCLUSIONLignin was degraded in vitro by the action of MnP and biomimetic systems initiating lipid peroxidation reactions. Application of the most reactive system, based on MnP, provided savings of 3.7 kg ClO2 ton(-1) pulp during ECF bleaching to 88-90% ISO brightness. (c) 2015 Society of Chemical Industry
Keywords: lignin; manganese peroxidase; oxidoreductases; lipid peroxidation; pulp bleaching; chlorine dioxide